1,090 publications and 5 years later: is FAP-targeted theranostics really happening? - Haberkorn, Uwe; Altmann, Annette; Giesel, Frederik L.; Kratochwil, Clemens (Journal of nuclear medicine, 2024)
Tumors consist of not only malignant cells but also stroma cells which include vascular and inflammatory cells and activated fibroblasts and may contribute up to more than 90% of the gross tumor volume in tumors with a strong desmoplastic reaction. A subpopulation of stroma cells called cancer-
Gesehen am 07.04.2025